Working Memory Depletion Affects Intertemporal Choice Among Internet Addicts and Healthy Controls - Li, Hongxia (Frontiers in Psychology, 2021)
Addiction to the Internet has emerged as a new kind of addictive behavior. Although previous studies have revealed that impairments in working memory led to suboptimal decision making (e.g., a greater willingness to choose smaller, more immediate rewards), little is known about how working memory affects intertemporal choice in Internet addicts and normal users. Thus, this study’s aim was to investigate the effect of working memory task on intertemporal decision makingchoice in 33 participants addicted to internet and 25 healthy controls. Participants were administered a) a test for Internet Addiction, b) a single delay discounting self-report questionnaire c) a working memory task. Differences between the Internet addicts and the control group were observed in terms of delay discounting rates, reaction times, and in memory accuracy rates. We observed significantly higher delay discounting rates among individuals addicted to the Internet. Moreover, it was documented that reaction times follow the 4-level working memory condition were significantly longer than follow the 2-level condition, in both the Internet addicts and the control group. The current findings suggest that Internet addicts are more likely to make short-sighted decisions than normal Internet users. The higher the level of working memory, the more likely an individual is to choose the present smaller reward, thus making short-sighted decisions, and have longer response times.